Fundamentals of Stock Price in Nepalese commercial banks (The International Research Journal of Management Science, 2019)
The aim of this study is to ascertain the determinants of the stock market price in Nepalese commercial banks for the period of 2065/66 to 2074/75. It is based on pooled cross-sectional data of ten banks for 10 years whose stocks are listed in Nepal stock exchange. The study employed correlational and causal comparative research design and result reveals that book value per share, price earnings ratio, return on equity have positive relationship with stock price. Dividend yield has positive but minimum influence on the price of the stock whereas size has negative relationship and is statistically insignificant with stock price. Further, it reveals that book value per share is a most influential factor that determines stock price in Nepal.